Treatment of Epstein-Barr virus-associated lymphomas: the role of Epstein-Barr virus-specific cytotoxic T cells (Hematology Meeting Reports, 2009)
Latent Epstein-Barr virus (EBV) infection is associated with a heterogeneous group of lymphoma, including Burkitt’s lymphoma, Hodgkin’s disease, NK-T lymphomas and lymphoproliferative disease (LPD).1-3 All EBV-associated malignancies are associated with the virus’ latent cycle, and three distinct types of EBV latency have been characterized.4,5 All are EBER positive, but the EBV latent protein expression varies. Latency type III, is expressed in lymphoblastoid cell lines (LCL), which can be readily produced by infecting B cells in vitro with EBV and is characterized by expression of the entire array of nine EBV latency proteins: EBNAs 1, 2, 3A, 3B, 3C, LP, BARF0 and the two viral membrane proteins LMP1 and LMP2.